Prognostic role of serum uric acid levels in patients with decompensated chronic heart failure - Sharma, Salvi; Priyadarshi, Basudev Prasad; Sachan, Mohit (International Journal of Research in Medical Sciences, 2024)
Background: Chronic heart failure (CHF) affects over 26 million people worldwide and is characterized by the heart’s inability to meet the body’s metabolic demands due to structural or functional abnormalities, resulting in high morbidity and mortality. Traditional biomarkers such as sST2, cardiac troponin, and natriuretic peptides are costly and not universally accessible, creating a need for affordable and accessible alternatives. Methods: This study evaluated the prognostic role of serum uric acid levels in decompensated CHF by comparing outcomes such as hospitalization duration, ICU stay, and mortality between patients with high (>7 mg/dl) and low (≤7 mg/dl) uric acid levels. Conducted over 14 months at K.P.S. Post Graduate Institute, GSVM Medical College, Kanpur, the study included 126 patients selected through purposive sampling. Data collection involved physical exams, laboratory tests, echocardiography, and ECGs. Results: Elevated serum uric acid levels were associated with reduced ejection fraction, prolonged hospital and ICU stays, and worse cardiac function. Patients with higher uric acid levels demonstrated poorer clinical outcomes, highlighting its potential role in risk stratification and prognosis. Conclusions: Serum uric acid is a valuable, low-cost prognostic marker for CHF, offering potential utility in early diagnosis and management. Its incorporation into clinical practice could improve outcomes and facilitate timely, affordable interventions, addressing the growing global burden of CHF. These findings underscore the need for further research to explore its integration into clinical workflows.